Implementasi Nilai-Nilai Islam Nusantara dalam Pendidikan Multikultural di Lingkungan Sekolah Islam Terpadu Al-Fatih Sukabumi - Atam Supatma; Santi Susanti; Ikal Ludya Hakim; Imam Asrofi; Neng Reni Rizki; Dewi Triani; Selvi Anggraeni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of Nusantara Islamic values ​​in multicultural education within the Integrated Islamic School (SIT) Al-Ftih environment. Nusantara Islam, as a religious concept characterized by moderation, tolerance, and accommodating local culture, has high relevance in developing education that respects diversity.Meanwhile, multicultural education emphasizes equality, inclusivity, and recognition of students' cultural identities.This research employed a qualitative approach with a case study method. Data collection techniques included interviews, observation, and documentation, and its validity was tested through triangulation. The study results indicate that the integration of Nusantara Islamic values ​​in SIT Al-Fatih Sukabumi remains partial, primarily limited to thematic religious activities and has not yet systematically addressed the curriculum, pedagogy, or school culture. Supporting factors for implementation include the availability of local culture, support from some teachers, and religious moderation policies. Inhibiting factors include a lack of teacher training, the dominance of Middle Eastern Islamic references, and a lack of multicultural evaluation instruments.This study concludes that a comprehensive implementation model that integrates Islam Nusantara into the curriculum, learning, and school culture is needed. Recommendations include developing standard operating procedures (SOPs) for religious moderation based on local wisdom, teacher training, and developing evaluation instruments for the internalization of Islam Nusantara values.